Nitric oxide in coronary artery disease: Effects of antioxidants - Tousoulis, D; Antoniades, C; Stefanadis, C (2006)
In this review article we examine the main mechanisms leading to decreased nitric oxide (NO) bioavailability, and we present the current strategies available to increase NO levels, mainly by using antioxidants in patients with coronary artery disease. Decreased NO bioavailability in the vasculature is a key feature of all the classic risk factors for atherosclerosis, and it can be the result of NO's decreased synthesis and increased oxidative deactivation. Increased NO synthesis can be achieved by improving the intracellular redox state in endothelial cells, stabilizing endothelial NO synthase (eNOS) dimers, and maintaining sufficient intracellular levels of eNOS substrate L-arginine. Antioxidant treatment may have a dual role by increasing NO synthesis and decreasing its oxidative deactivation. However, in patients with coronary artery disease, although intracoronary infusions of vitamins or chronic vitamin treatment improve endothelial function, their effect on clinical outcome is questioned. In conclusion, in coronary artery disease, NO bioavailability can be increased mainly by reversing the causes of endothelial dysfunction via treatment of classic risk factors, while the use of antioxidant vitamins is controversial and the ideal antioxidant strategy is still unknown. © Springer-Verlag 2005.